Implementasi Prototipe Sistem Monitoring Tempat Parkir Mobil dengan Metode Time Division Multiple Access (TDMA) berbasis NRF24L01 - Resya Wakhid Ardiansyah; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
In this decade, the number of vehicles, especially cars, has increased very rapidly. Every year the number of vehicles increases by 5% including passenger cars, with this rapid growth making parking lors increasingly limited and uncontrolled. With the use of Wireless Sensor Networks (WSN) can perfrom measurable data collection with many predetermined nodes, with many of these nodes will cause problems in sending data that will collide with each other. The use of the Time Division Multiple Access (TDMA) method on all nodes will overcome the problem of conflicting data, the use of this medhotd is also based on the Time-Sync Protocol for Sensor Networks (TPSN) which is able to make all nodes have the same local time to make it easier to send data. The functional testing results of the root nde, server node, and 3 sensor nodes successfully carry out the functionality properly. Three performance tests were conducted, namely time synchronization accuracy, timeslot scheduling performance, and success ratio in detecting parking vehicles. The results of testing the accuracy of time synchronization with the TPSN protocol obtained time accuracy results of 700-800ms. Test results of timeslot scheduling performance with TDMA method, data can be sent and in accordance with timeslot by 91,6%. And the test results of the success ratio in detecting parking vehicles in 20 trials of 95%.